Pelatihan Kader Kesehatan Posbindu Menuju Posbindu Mandiri - Wijayanti Wijayanti; Retno Dewi Noviyanti; Dodik Luthfianto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Non-communicable diseases (PTM) are diseases that cannot be transmitted from person to person, whose development progresses slowly over a long period of time (chronic). In the early stages, PTM is often asymptomatic, many do not know and are aware that they have PTM, thus making public awareness for self-examination/early detection lacking. Posbindu PTM activities to increase community participation in prevention and early detection of PTM risk factors through training of Posbindu health cadres including general health assessments, nutritional assessments and provision of additional food made from local ingredients. Health cadres are the spearhead of Posyandu implementation. The existence of health cadres plays a major role in the implementation of Posyandu so that it is necessary to increase the knowledge and skills of health cadres to support the implementation of Posbindu PTM. The purpose of this community service is the transformation of knowledge and skills regarding Posbindu management for the detection of NCDs through health checks and examinations of nutritional status and the provision of additional meals. The community service method is Posbindu cadre training in the form of knowledge and skills transformation on Posbindu management for PTM detection and provision of additional meals. The target is the health cadres of Posbindu Salak, Songgorunggi Hamlet, RT.01 RW.06, Dagen Village, Jaten District, Karanganyar Regency, totaling 15 personnel, held on December 28, 2022. The results of the activity showed that there was an increase in the knowledge of the training participants by 100%, namely the pretest results where the lowest score was 40 and the highest score was 80 and the average pretest score was 58.85, while the posttest score was the lowest score 80 and the highest score was 100 and the average the average posttest value is 91.92 so that the lowest increase is 15 and the highest increase is 55 and the average increase is 33.